Optimasi Query Sistem Informasi Menggunakan Stored Procedure - Tri Hastono (Jurnal Dinamika Informatika, 2019)
Queries are used for operations on information systems that use a database as data storage. The importance of queries should be a major concern at the application design stage. Generally the application designer ignores it so applications that are made will have poor performance when the data in the database is getting bigger. To overcome the decline in application performance because of neglecting query design, query optimization is performed. This study provides a solution to the declining performance of information systems by optimizing query information systems using stores procedures. The database in this study is designed by using MySQL Server 5 with 12 tables. The store procedure chosen in this study is function. There are 13 functions created with 12 functions for each table and 1 function to capture the status of the database operation processes.